Liver Transplantation during Pregnancy for Acute Liver Failure due to HBV Infection: A Case Report. (9th December 2013) - Kimmich, Nina; Dutkowski, Philipp; Krähenmann, Franziska; Müllhaupt, Beat; Zimmermann, Roland; Ochsenbein-Kölble, Nicole
Abstract : Acute hepatic failure during pregnancy is a life-threatening situation for the mother and fetus and might need a super-urgent liver transplantation. Many pregnancies with positive outcomes are reported after a previous liver transplantation before the pregnancy, but only a few of them are mentioned with transplantation during pregnancy. In these few cases, fetal outcome is mostly adverse. Experience with liver failure during pregnancy and its management is still deficient and needs to be approved. For sure, patients need to be treated in highly qualified centers in a multidisciplinary approach. We present a case of successful super-urgent liver transplantation during the second trimester of pregnancy after acute hepatic failure due to an acute hepatitis B infection with positive maternal and fetal outcome. Liver transplantation during pregnancy due to an acute liver failure can be a life-saving procedure for the mother and fetus. An early initiated maternal therapy with antiviral drugs and immunoglobulins seems to be safe and able to prevent fetal infection and immunosuppressive therapy after transplantation seems to be well tolerated. Nevertheless, fetal outcome differs widely and long-term outcome is deficiently known.